A Moderated-Mediation Analysis of Organizational Justice and Leader-Member Exchange: Cross-Validation With Three Sub-samples - Shkoler, Or; Tziner, Aharon; Vasiliu, Cristinel; Ghinea, Claudiu-Nicolae (Frontiers in Psychology, 2021)
In an increasingly competitive work world, managers – whose links with subordinates, and their perceptions thereof, are critical components in that relationship – need to monitor their employees’ mindsets to facilitate their productivity. In the current paper, perceptions of organizational justice are investigated as a precursor to two significant outcomes, organizational citizenship behavior and counterproductive work behavior. The moderating effect of LMX and the mediating effects of work motivation were incorporated into a parsimonious moderated-mediation model designed to assist managers in achieving the stated objective. The model was tested on 3293 Romanian workers, randomly divided into sub-samples of 1098, 1098, and 1097 participants. Indicating high data consistency and credibility for the most part, in each sub-group, all the variables associated as predicted, with the notable exception of LMX. Implications, limitations, and suggestions for future research are discussed, with emphasis on the investigation’s cultural context.